2020
DOI: 10.1007/s00338-020-01917-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale delineation of Symbiodiniaceae genotypes on a previously bleached central Red Sea reef system demonstrates a prevalence of coral host-specific associations

Abstract: Widespread coral bleaching occurred in the central Red Sea in 2010 and 2015. During both events, a cross-shelf and depth gradient of bleaching severity was identified within the Thuwal reef system, central Red Sea, Saudi Arabia. While bleaching and survival of coral taxa were monitored, neither in situ reef temperatures nor coralassociated algal communities (family Symbiodiniaceae) were characterized. Here, we determined coral host-associated Symbiodiniaceae communities and monitored temperatures along the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 51 publications
5
40
1
Order By: Relevance
“…3B). The observed pattern of symbiont association indicates high host delity of algal symbionts across sites, as reported previously (Terraneo et al 2019;Howells et al 2020;Hume et al 2020). Further to that, our results support ne-scale differentiation even between geographically close-by sites, as the central Red Sea sites (AF, ExT, ExP) all differed with regard to symbiont identities (Fig.…”
Section: Thermally Stable Site-speci C Algal Symbiont Communitiessupporting
confidence: 91%
See 2 more Smart Citations
“…3B). The observed pattern of symbiont association indicates high host delity of algal symbionts across sites, as reported previously (Terraneo et al 2019;Howells et al 2020;Hume et al 2020). Further to that, our results support ne-scale differentiation even between geographically close-by sites, as the central Red Sea sites (AF, ExT, ExP) all differed with regard to symbiont identities (Fig.…”
Section: Thermally Stable Site-speci C Algal Symbiont Communitiessupporting
confidence: 91%
“…At large, the level of responsiveness in algal symbionts from GoA corals was unexpected, given that the common notion is that of a paucity of regulation at the transcriptional level for Symbiodiniaceae (Bayer et al 2012;Baumgarten et al 2013), signi ed by xed expression differences between symbiont genera and species (Barshis et al 2014;Parkinson et al 2016). Notably, corals from all sites associated with distinct and largely consistent microalgal symbiont genotypes, suggesting host delity and local adaptation (Howells et al 2020;Hume et al 2020). Despite the differences across sites, the consistent gene expression stasis of algal symbionts across CRS corals and the disparate responsiveness in Symbiodiniaceae from GoA corals potentially suggests that geographically more distant symbionts are also more differentiated.…”
Section: Signatures Of Thermal Tolerance Across Regions and Coral Holmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Likewise,Hume et al (2020) reported similar cool biases (~0.5 to >1°C) in satellites compared to reef temperatures across the shelf in the Thuwal area of the central Red Sea, approximately 300 km north of the Farasan Banks. Together, this suggests that satellite-derived SST in portions of the Red Sea may substantially underestimate reef-water temperatures.…”
mentioning
confidence: 57%
“…However, most Symbiodiniaceae are recalcitrant to culturing (Coffroth, 2005; Krueger & Gates, 2012; Santos et al., 2001), and not all free‐living Symbiodiniaceae can initiate symbiosis (Coffroth et al., 2006; LaJeunesse, 2002; Yamashita et al., 2014), therefore these early studies likely underestimated diversity. Next generation sequencing (NGS) has revolutionised community‐level assessments of marine dinoflagellates, uncovering extensive cryptic biodiversity (Hume et al., 2020; Kohli et al., 2014; Stern et al., 2010) and is increasingly utilised to profile in hospite Symbiodiniaceae community structure (Boulotte et al., 2016; Camp et al., 2020; Hume et al., 2020; Thomas et al., 2014; Ziegler et al., 2017). Few studies have leveraged NGS for free‐living Symbiodiniaceae characterisation.…”
Section: Introductionmentioning
confidence: 99%